THE EFFECT OF THE ACTIVITY ON THE DISTRIBUTION OF CARDIOACTIVE GLYCOSIDES IN THE ORGANISM - POZO, EFREN C DEL (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1949)
Expts with 80 cats injected with "Estrofosid" (Sandoz) show that the lethal dose of digitalis in the animal with skeletal muscle electrically stimulated is significantly higher than without such activation, indicating fixation of digitalis in that muscle
BOL INST ESTUD MED BIOL
Keywords: EFFECT, ACTIVITY, CARDIOACTIVE, GLYCOSIDES, ORGANISM; CIENCIAS MEDICAS; MEDICINA INTERNA; CARDIOLOGIA